2017
DOI: 10.1007/s00127-017-1385-x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of narrative enhancement and cognitive therapy: a randomized controlled study of a self-stigma intervention

Abstract: PurposeStigma has been proposed to be one of the most serious obstacles to successful treatment, rehabilitation and inclusion in society of people with severe mental illness. An aspect of stigma which has been increasingly discussed is self-stigma, which refers to the internalization of negative stereotypes among people with severe mental illness. The aim of the present study was to investigate the effectiveness of a group-based anti self-stigma intervention, narrative enhancement and cognitive therapy (NECT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 33 publications
6
63
1
6
Order By: Relevance
“…This positivity and group cohesiveness is reflected in the zero withdrawal rate and high attendance. This result aligns with the recommendations to focus on group climate to improve attendance (Hansson et al 2017).…”
Section: Research Questionsupporting
confidence: 84%
See 1 more Smart Citation
“…This positivity and group cohesiveness is reflected in the zero withdrawal rate and high attendance. This result aligns with the recommendations to focus on group climate to improve attendance (Hansson et al 2017).…”
Section: Research Questionsupporting
confidence: 84%
“…There is a small yet growing evidence base on the effectiveness of NECT. The manual was piloted in the United States (Roe et al 2010;Yanos et al 2012), Israel (Roe et al 2014), and Sweden (Hansson and Yanos 2016;Hansson et al 2017). It was delivered to individuals with schizophrenia, schizoaffective, bipolar disorders, and major depression.…”
Section: Narrative Enhancement and Cognitive Therapy (Nect)mentioning
confidence: 99%
“…At re-assessment after the interventions, the participants' self-esteem scores were significantly higher than at baseline in both samples. The participants had improved on other measures as well, such as quality of life and activity engagement in Sample 1 [21] and reduced stigma in Sample 2 [22], which supports that the RSES detected a true change. The evidence of the ability of RSES to detect change is also acknowledged in other research [15,48].…”
Section: Discussionmentioning
confidence: 62%
“…Sample 2 consisted of participants in a study investigating the effectiveness of a group-based anti-self-stigma intervention, narrative enhancement and cognitive therapy (NECT), with regard to changes in self-stigma, self-esteem, and subjective quality of life [22]. NECT is a structured, group-based intervention comprising 20 weekly 1-h sessions [23].…”
Section: Participantsmentioning
confidence: 99%
“…Therefore, changes to an individual's self-narrative are theorised to reduce self-stigma. Randomised controlled trial evaluations of NECT have shown a positive impact on self-stigma, and associated outcomes such as hope, self-esteem and quality of life [17,18].…”
Section: Introductionmentioning
confidence: 99%